Purple Corn (Zea mays indurata) Ice Cream as an Immune Booster in The Pandemic Era - Faza Saiqur Rahmah; Fitriyani Fitriyani; Lisa Aulia Zahra; Muhamad Abdulloh Umar; Muhammad Abbas Arriziq; Burhan Ma'arif (University of Sultan Ageng Tirtayasa, 2022)
The COVID-19 pandemic has had an impact on public health. Immune resistance was a crucial factor in the pandemic era considering all diseases that arise as self-limiting diseases. Food as a source of nutrients had a vital role as an immunomodulator. As an agricultural country with food production commodities that were still massive, agricultural products are needed to develop food innovations, such as purple corn. One of the nutritional contents of purple corn was the flavonoid group in the form of anthocyanin compounds as a source of antioxidants to increase the body's immunity and prevent diseases caused by viruses, fungi, and bacteria, as well as prevent atherosclerosis, gastric damage, cholesterol, obesity, and others. Anthocyanin compounds in purple corn 70mg/100 grams. Anthocyanins in purple corn are processed into healthy food in ice cream with the product label